Main effects of sleep disorders related to shift work-opportunities for preventive programs - Bajraktarov, Stojan; Novotni, A; Manusheva, Nensi; Gudeva Nikovska, Danche; Miceva-Velickovska, Elizabet; Zdraveska, Natasha; Samardjiska, Valentina C; Richter, Kneginja S (Springer Science and Business Media LLC, 2011)
The sleep-related problems of shift workers usually occur as transient phenomena related to the timing of work. Sleep disorders, related to sleep deprivation, have a major impact on the quality of life and health status of healthcare workers. Reduced quantity and quality of sleep negatively affects the activities of shift workers, particularly in terms of their social functioning, quality of life and health. However, it seems that health authorities and the medical staff are negligent when it comes to the negative effects on health caused by work in night shifts. Recently published studies in this field suggest that appropriate public health preventive programs dealing with sleep disorders successfully contribute towards the quality of life of workers.